Statelessness in the European Union : displaced, undocumented, unwanted - Sawyer, Caroline, 1962-; Blitz, Brad K. (Cambridge : Cambridge University Press, 2011)
'This work looks at the phenomenon of statelessness in Europe from a number of different perspectives. In the first instance it explores the legal position of statelessness in European and international law. It then provides a contemporary account of displaced populations in the European Union, drawing on case studies from the'old' and the'new' Europe: France, the United Kingdom, Estonia and Slovenia. Finally the editors suggest how the European Union might develop a legal response to statelessness. This innovative and important study will be of huge interest to European lawyers specialising in immigration and citizenship and to political scientists in the field. It will also appeal to international and human rights lawyers'--
Statelessness in the European Union / Brad K. Blitz and Caroline Sawyer -- Stateless people and undocumented migrants : an Arendtian perspective / Monika Krause -- The rights of non-citizens to membership / Matthew J. Gibney -- Stateless in Europe : legal aspects of de jure and de facto statelessness in the European Union / Caroline Sawyer -- Policy responses and global discourses on the rights of non-citizens and stateless people / Brad K. Blitz -- Research design and methodology of the country studies / Caroline Sawyer and Brad K. Blitz -- De facto statelessness in the United Kindom / Caroline Sawyer, Brad K. Blitz and Miguel Otero-Iglesias -- Non-citizens in Slovenia : erasure from the register of permanent residents / Jelka Zorn -- The statelessness issue in Estonia / Raivo Vetik -- The sans papiers in France / Arnaud Lucien, David Marrani and the editors -- Analysis : the practical and legal realities of statelessness in the European Union / Brad K. Blitz and Caroline Sawyer -- Conclusions / Caroline Sawyer and Brad K. Blitz.
Includes bibliographical references (pages 312-334) and index.
Keywords: Stateless persons -- Legal status, laws, etc. -- European Union countries; Emigration and immigration law -- European Union countries